Joint Pricing and Inventory Decisions for Constant Priced Items - Kunreuther, Howard; Schrage, Linus (Management Science, 1973)
This paper develops an algorithm for determining the pricing and ordering decisions for a firm that produces one product for which there is a deterministic demand curve that differs from period to period. It is assumed that the firm wants to maintain the same price for the product throughout the season. There is a fixed cost associated with each order placed (or alternatively, each batch produced) in addition to per unit ordering and storage costs for carrying inventory over time.